Malakoplakia cervix misdiagnosed as Carcinoma cervix (Bangladesh Journal of Medical Science, 2014)
Malakoplakia cervix is still not reported in literature. Inflammatory lesions of cervix on visible appearance mimic as cervical malignancy. Histopathology confirms the diagnosis. Aim is to highlight the fact that errors occur in medical practice, if all differential diagnosis are not thought. A proper histopathological diagnosis is mandatory before final diagnosis. DOI: http://dx.doi.org/10.3329/bjms.v13i2.14884 Bangladesh Journal of Medical Science Vol.13(2) 2014 p.215-217